Cast for eternity : bronze masterworks from India and the Himalayas in Belgian and Dutch collections (2005)
[Dt.:] Die Ausstellung "Cast for Eternity" wurde vom Ethnologischen Museum in Antwerpen organisiert und ausgerichtet. Dabei wurden Bronzedarstellungen aus Indien, Nepal, Tibet und Sri Lanka gezeigt. Die zudem entstandene Online-Ausstellung ist regional in drei Abschnitte (Indien und Sri Lanka, Nepal, Tibet) eingeteilt. Neben erklärenden Texten zu allen Exponaten steht auch für jede Sektion ein einführender Text zur Verfügung. Auch die gesamte Ausstellung wird mit einer separaten Einleitung und einem Essay eröffnet. - [Engl.:] The selection of bronze sacred images in the exhibition Cast for Eternity represents an important reflection of the cultural heritage of India, Sri Lanka, the Himalayas, and Tibet, countries and regions which have occupied their own significant places in the art history of the world for over 2000 years. The sensuality, spirituality and beauty of these images are emphasized by the highly technical development and skilful exploitation of bronze casting techniques. As if they have been created for eternity, the bronzes radiate a sense of immortality and reflect the fascination and mystery of the ancient cultures of Buddhism, Jainism and Hinduism. The online exibition is divided in three parts (India, Nepal, Tibet). Jan van Alphan and Marcel Nies introduce in the exhibition with essays.